Treating Treatment-Resistant Obsessive-Compulsive Disorder (OCD) via Deep Brain Stimulation (DBS) - Wong, Wing Hei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Obsessive-Compulsive Disorder (OCD) is a prevalent and challenging mental health condition characterized by persistent, unwanted thoughts (obsessions) and repetitive behaviors (compulsions). Traditional treatment modalities, including pharmacotherapy and cognitive-behavioral therapies, fail to alleviate symptoms in around half of the patients, necessitating the exploration of alternative therapeutic options. Deep Brain Stimulation (DBS) has emerged as a promising intervention for treatment-resistant OCD, with recent studies reporting a success rate of about 60%. This innovative treatment involves the precise placement of electrodes in specific brain regions such as the Nucleus Accumbens (NAcc), Bed Nucleus of the Stria Terminalis (BNST), and Subthalamic Nucleus (STN) to modulate dysfunctional neural circuits. This paper reviews the effectiveness of DBS in reducing OCD symptoms, evaluates its safety, and discusses the neurobiological mechanisms underlying its therapeutic effects. It also explores future research directions, including the optimization of electrode placement, the integration of DBS with other treatment modalities, and the development of personalized medicine approaches. Furthermore, the paper addresses ongoing challenges such as the need for a clearer understanding of DBS mechanisms, the refinement of patient selection criteria, and the management of long-term outcomes. By providing a comprehensive overview of current knowledge and potential developments, this study aims to highlight the role of DBS as a transformative tool for managing severe, refractory OCD.